Individualized management of extraperitoneal bladder perforation after transurethral resection of bladder tumor: a report of two distinct cases - Giovis, Georgios; Panagiotopoulou, Georgia; Vlachopanos, Georgios; Chondros, Kostas (International Surgery Journal, 2019)
Transurethral resection of bladder tumor represents the most common cause of bladder injury. Several factors such as the presence of a tumor itself, the wall thickness, the use of extensive cautery or obturator nerve jerk may lead to bladder perforation. Due to the anatomical site of the bladder, the perforation is extraperitoneal in most of the cases and bladder catheterization alone is sufficient for treatment. In several cases, urine reabsorption can be life-threatening and therefore more active treatment is needed. We present two distinct cases of extraperitoneal bladder perforation which presented with a different clinical image and were treated unexpectedly.